COMPARING THE ORGANIZATIONAL INFRASTRUCTURE FOR INSTRUCTIONAL LEADERSHIP IN NATURAL SCIENCES TEACHING AMONG FORMERLY SEGREGATED SCHOOLS IN GAUTENG - Cynthia B Malinga; Loyiso C Jita; Abiodun A Bada (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2022)
School organizational conditions influence teaching and learning. Instructional leadership is context-based, and the practices of the leader are contingent upon the school’s organizational context. In this paper, we examine how different schools create the organizational infrastructure for teaching and learning natural sciences (NS) and the adequacy thereof in providing a supportive environment for the teachers and students in the subject. Using a mixed methods approach, we compare the extent to which the organizational infrastructures in schools enable and/or constrain NS instruction and its leadership. We use survey data on NS teachers and their heads of department on school conditions and infrastructures, management and administrative processes, and subject leadership practices. A total of 77 schools and 15 participants responded to the questionnaire and participated in the interview/observation respectively, from 4 districts in the Gauteng province of South Africa. The data obtained were analyzed using descriptive statistics and content analysis. The findings showed that schools sharing similar socio-economic contexts have similar organizational infrastructures and arrangements around which the core work of teaching and learning was organized. The study concludes that school organizational infrastructures (shaped by contexts) may either promote or constrain effective instructional leadership for NS. We recommend that schools need to review their organizational arrangements and infrastructures to support instructional leadership and enhance their capacity to strengthen NS instruction more effectively.